2009
DOI: 10.1007/s10509-009-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Energy contents of some non-vacuum spacetimes in teleparallel gravity

Abstract: This paper elaborates the problem of energymomentum in the framework of teleparallel equivalent of General Relativity. For this purpose, we consider energymomentum prescription derived from the integral form of the constraint equations developed in the Hamiltonian formulation of the teleparallel equivalent of General Relativity. We use this technique to investigate energy-momentum of stationary axisymmetric Einstein-Maxwell solutions and cosmic string spacetimes. The angular momentum, gravitational and matter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…and the teleparallel gravity theory (TEGR) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] also have very wide applications. We notice the similarity and connections between the results obtained with different pseudotensorial definitions and the teleparallel gravity theory (TEGR) [46][47][48][49][50].…”
mentioning
confidence: 99%
“…and the teleparallel gravity theory (TEGR) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] also have very wide applications. We notice the similarity and connections between the results obtained with different pseudotensorial definitions and the teleparallel gravity theory (TEGR) [46][47][48][49][50].…”
mentioning
confidence: 99%
“…Sharif and his collaborators [39][40][41] found that the results for the energy exactly coincided with several prescriptions in GR. Interestingly, our results exactly coincide with different energy-momentum prescriptions in GR.…”
Section: Introductionmentioning
confidence: 58%
“…Vargas [28] found that the total energy of the closed Friedmann-Robertson-Walker model was zero by using the TP version of Einstein and Landau-Lifshitz complexes which agreed with the results of GR [31]. Sharif and his collaborators [24], [33][34][35][36][37][38][39][40][41] used different prescriptions to determine the energy-momentum distributions for various spacetimes and found that the results of TPG and GR were not consistent. Recently, Amir and his collaborators [42] evaluated the energy-momentum distribution of non-static plane-symmetric spacetimes by using different prescriptions in the context of TPG and GR and showed that the results for the Einstein, Landau-Lifshitz, Bergmann-Thomson prescriptions are the same in both the theories but are different form those obtained when using the Möller prescription.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The Weitzenböck connection (Sharif andTaj 2010a, 2010b) and corresponding torsion tensor are defined in terms of tetrad field e a μ as λ μν = e a λ ∂ ν e a μ ,…”
Section: Energy-momentum Through Hamiltonian Approach In Teleparallelmentioning
confidence: 99%
“…In this framework, Maluf et al (2002) defined gravitational energy, momentum and angular momentum using the literature (Maluf 1994). Adopting this procedure, many people (Maluf et al 2003;da Rocha-Neto and Castello-Branco 2003;Sharif andTaj 2010a, 2010b) computed energy and its contents for different solutions. Recently, we have also investigated energy and its relevant quantities for a class of regular black holes coupled with non-linear electrodynamics source (Sharif and Jawad 2010).…”
mentioning
confidence: 99%